Low‐Temperature Preparation of a Mesoporous Silica Superbase by Employing the Multifunctionality of a La2O3 Interlayer. Issue 9 (8th February 2017) - Liu, Ning; Wu, Zhimin; Li, Meng; Li, Shanshan; Luo, Zhantao; Li, Yongfei; Pan, Langsheng; Liu, Yuejin
Abstract: A simple and effective approach for the preparation of the solid superbasic La2 O3 –SBA‐15‐supported KF (KF/La2 O3 –SBA‐15) was developed by a low‐temperature strategy. The KF/La2 O3 –SBA‐15 with ordered mesostructure and a high base strength ( H − =27.0) was realized at 350 °C in still air, which breaks the traditional method of thermally induced decomposition of basic metal nitrate derived species KNO3 under higher temperatures (>600 °C). The resultant mesoporous basic materials were adopted for the production of 1‐methoxy‐2‐propanol from propylene oxide and methanol. It showed excellent catalytic performance exhibiting 93 % conversion of propylene oxide and 93 % selectivity to 1‐methoxy‐2‐propanol. This performance is better than that over the catalysts without mesoporous silica despite having a higher KF content. Abstract : Resisting the structural collapse : Mesostructured superbasic sites were generated by employing the formation of La2 O3 –SBA‐15‐supported KF through thermal treatment at a low activation temperature of 350 °C under air atmosphere.